Mutation profiles of diffuse large B‐cell lymphoma transformation of splenic B‐cell lymphoma/leukemia, unclassifiable on whole‐exome sequencing. Issue 4 (13th October 2021) - Kurosawa, Shuhei; Toya, Takashi; Sadato, Daichi; Hishima, Tsunekazu; Hirama, Chizuko; Najima, Yuho; Kobayashi, Takeshi; Haraguchi, Kyoko; Okuyama, Yoshiki; Oboki, Keisuke; Harada, Hironori; Sakamaki, Hisashi; et al.
Abstract: A 58‐year‐old male was diagnosed with splenic B‐cell lymphoma/leukemia, unclassifiable (SPLL‐U). The lymphoma transformed into diffuse large B‐cell lymphoma (DLBCL), and multidrug chemotherapy and autologous stem cell transplantation achieved complete remission. Two years later, the lymphoma relapsed as SPLL‐U. Serial whole‐exome sequencing indicated that the mutation profiles were similar between the onset and relapsed samples while those in DLBCL were partially distinctive, which was in line with the clinical course. Hierarchical clustering revealed that an IGLL5 mutation was the founder mutation proceeding the development of the diseases and suggested that KRAS and other mutations might contribute to the transformation.